Method for decomposing polyester resin
Patent Information
- Application Number
- JP2023086516
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-05-25
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-05-25
AI Technical Summary
Existing methods for depolymerizing polyester resin, such as hydrolysis and alcoholysis, face issues with high costs due to the use of expensive chemicals and corrosion of equipment, and inefficient recovery of ethylene glycol under alkaline or acidic conditions.
Hydrolyzing polyester resin in neutral reaction water using a solid oxide or hydroxide with a higher standard redox potential than water, such as lead oxide or nickel oxide, to create an acidic environment at the solid-liquid interface, thereby depolymerizing the resin without expensive chemicals.
This method allows for the efficient production of low-molecular monomers like terephthalic acid and ethylene glycol at a lower cost, utilizing inexpensive water and common oxides as catalysts, and can convert ethylene glycol to methanol under controlled conditions.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for decomposing a polyester resin. [Background technology]
[0002] Plastics are easy to mold and can be mass-produced at low cost, so they are used as materials for a variety of products. However, a large amount of them is discarded, and the disposal of waste plastics is an urgent issue. Traditionally, waste plastics have been incinerated or crushed / pulverized before being disposed of in landfills. However, as the amount of waste plastic increases, there is a shortage of facilities to incinerate or crush / pulverize waste plastics, and it is also difficult to secure landfill sites for processed plastics. Therefore, rather than disposing of waste plastics, recycling them into useful materials and using them is being considered.
[0003] One method for recycling plastics is chemical recycling, which involves changing the molecular structure of collected waste plastics so that they can be reused. Polyester resin is one of the most widely produced plastics, and since there is a relatively well-established social system for sorting and collecting it, technological development for chemical recycling has been progressing more quickly than for other plastics.
[0004] One of the chemical regeneration methods for polyester resin is to chemically depolymerize polyester resin to convert it into low molecular weight monomer components. For example, Non-Patent Document 1 discloses hydrolysis, alcoholysis (methanolysis), aminolysis, ammoniaysis, and ethylene glycolysis as examples of methods for depolymerizing polyethylene terephthalate (PET), which is a polyester resin. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] U.S. Patent No. 4,605,762 [Non-patent literature]
[0006] [Non-Patent Document 1] Gopel Jeya, et al., "A short review on latest developments in catalytic depolymerization of Poly(ethylene terephathalate) wastes." J. of the Indian Chemical Society 99(2022)100291 Summary of the Invention [Problem to be solved by the invention]
[0007] The hydrolysis method is a method in which PET is hydrolyzed using water as a medium under alkaline or acidic conditions to recover terephthalic acid (TPA) and ethylene glycol (EG). In order to increase the recovery efficiency in the hydrolysis method, it is necessary to make the conditions more alkaline or acidic, but under such conditions, although the recovery efficiency of TPA increases, EG is decomposed and cannot be recovered. In addition, there is a problem that making the conditions more acidic causes corrosion of equipment such as metal reactors and piping.
[0008] In the alcoholysis method, aminolysis method, ethylene glycolysis method, and ammonolysis method, alcohol (methanol), organic amines, diols, and ammonia are used to depolymerize PET, respectively. However, since alcohol (methanol), organic amines, diols, and ammonia are all useful chemical substances, using useful chemical substances to recycle PET goes against the purpose of recycling. In addition, since alcohol (methanol), organic amines, and diols are relatively expensive chemical substances, the monomer components obtained using such chemical substances are not competitive in terms of price.
[0009] The problem to be solved by the present invention is to provide a technique capable of decomposing polyester resins at low cost without using useful and expensive chemical substances as materials. [Means for solving the problem]
[0010] The method for decomposing a polyester resin according to the present invention, which has been achieved to solve the above problems, comprises the steps of: The polyester resin is brought into contact with a solid oxide or hydroxide having a higher standard oxidation-reduction potential than water (H2O) in neutral reaction water to hydrolyze the polyester resin.
[0011] In the present invention, the "neutral reaction water" is typically pure water, but may contain some impurities as long as they do not affect the depolymerization reaction of the polyester resin. In addition, the "neutral reaction water" does not have to be strictly neutral (pH=7), and water with a pH of about 6 to 8 is also included in the "neutral reaction water".
[0012] Examples of oxides or hydroxides with a higher standard redox potential than water (H2O) include lead oxide (PbO2), nickel oxide (NiO2, Ni3O4) and nickel hydroxide (Ni(OH)3). The reactions of lead oxide (PbO2), nickel oxide (NiO2, Ni3O4) and nickel hydroxide (Ni(OH)3) in water (H2O) and their respective standard redox potentials (E 0 ) are as follows (1) to (5).
[0013] (1)2H2O (liquid) ⇔ 4H + +4e - +O2E 0 =1.229V (2)PbO2(solid)+4H + +2e - ⇔ Pb2 + +2H2O E 0 =1.468V (3)NiO2(solid)+4H + +2e - ⇔ Ni2 + +2H2O E0 =1.68V (4)Ni3O4(solid)+8H + +2e - ⇔ 3Ni2 + +4H2O E 0 =1.997V (5)Ni(OH)3(solid)+3H + +e - ⇔ Ni2++3H2O E 0 =2.08V In the reaction equations (1) to (5) above, the two-way arrow symbol (⇔) represents equilibrium.
[0014] As can be seen from (1) to (5) above, the standard oxidation-reduction potentials (E 0 ) is the standard oxidation-reduction potential of water (E 0 ), the water molecules on the surface of the oxide or hydroxide solid can carry protons (H + ) and electrons (e - ) and oxygen (O2). This equilibrium occurs spontaneously without the need for external energy, so when solids such as lead oxide (PbO2), nickel oxide (NiO2, Ni3O4), and nickel hydroxide (Ni(OH)3) are placed in water, the solid surface (solid-liquid interface) becomes a strongly acidic environment.
[0015] However, only the solid-liquid interface becomes a strongly acidic environment, and the entire water (bulk) does not become an acidic environment. Therefore, in the decomposition method according to the present invention, the polyester resin is hydrolyzed by contacting the polyester resin with a solid surface in reaction water.
[0016] The oxide or hydroxide used in the decomposition method of the present invention has a standard oxidation-reduction potential (E 0 ) is sufficient, and in addition to the above-mentioned lead oxide (PbO2), nickel oxide (NiO2, Ni3O4), and nickel hydroxide (Ni(OH)3), for example, nickel oxyhydroxide NiO(OH), an active material for nickel-metal hydride batteries, can also be used.
[0017] The oxide or hydroxide solid used in the decomposition method of the present invention may have any shape as long as the solid surface can be brought into contact with the polyester resin. However, since the rate of polyester hydrolysis can be increased by increasing the contact area between the solid surface and the polyester resin, the solid is preferably in a granular or powdered form. In addition, the polyester resin to be treated should be as small as possible, and polyester resin products such as PET bottles should be crushed and pulverized into small pieces (chips) before hydrolyzing them using the decomposition method of the present invention. When the polyester resin is in a small piece form, the oxide or hydroxide solid may be relatively large, such as a plate or a block, other than granular or powdered form, but even in this case, the contact area with the small piece of polyester resin can be increased by making the solid granular or powdered form. Effect of the Invention
[0018] The method for decomposing a polyester resin according to the present invention focuses on the fact that water acts as an acid at the interface between a solid oxide or hydroxide having a higher standard redox potential than water, and utilizes this mechanism of action to acid-hydrolyze a polyester resin. That is, in the present invention, cheap and easily available neutral water is used for hydrolysis of the polyester resin, and a solid oxide or hydroxide is used as a solid-liquid interface catalyst. Therefore, it is possible to obtain low molecular weight monomers by depolymerizing the polyester resin at low cost without using useful and expensive chemical substances as materials. [Brief description of the drawings]
[0019] [Figure 1] Schematic diagram of the hydrolysis of PET in water using lead oxide (PbO2). [Diagram 2] Equation describing the reaction of ethylene glycol with hydrogen at the interface between lead oxide and water. [Diagram 3] Chromatogram of components contained in the filtrate obtained in Experimental Example 1. [Figure 4]Chromatogram of components contained in the filtrate obtained in Experimental Example 2. [Diagram 5] Chromatogram of components contained in the filtrate obtained in Experimental Example 3. [Figure 6] XRD spectrum of the material adhering to the surface of the lead oxide remaining on the filter. [Figure 7] XRD spectrum of commercially available disodium terephthalate. [Figure 8] XRD spectrum of the lead oxide powder remaining on the filter. [Figure 9] XRD spectrum of virgin lead oxide powder. [Figure 10] SEM image of virgin lead oxide. [Figure 11] Chromatogram of the components contained in the filtrate obtained in Experimental Example 4 when the reaction time was 1 hour. [Figure 12] Chromatogram of the components contained in the filtrate obtained in Experimental Example 4 when the reaction time was 3 hours. [Figure 13] Chromatogram of the components contained in the filtrate obtained in Experimental Example 4 when the reaction time was 6 hours. [Figure 14] Chromatogram of components contained in the filtrate obtained in the comparative example. [Figure 15] XRD spectrum of the material adhering to the surface of the lead oxide remaining on the filter. [Figure 16] XRD spectrum of commercially available disodium terephthalate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The method for hydrolyzing a polyester resin according to the present invention will now be described in detail. Fig. 1 is a schematic diagram showing a method for hydrolyzing polyester resin according to the present invention. In Fig. 1, granular lead oxide (PbO2) is used as the solid oxide, and small pieces (PET chips) obtained by crushing and pulverizing products such as PET bottles are used as the polyester resin. The granular lead oxide and the PET chips are placed in a reaction vessel (not shown) containing water, and are in contact with each other in the water.
[0021] When the granular lead oxide and PET chips are in the above state, due to the difference between the standard redox potential of lead oxide and the standard redox potential of water, water acts as an acid at the interface between the solid lead oxide and water (solid-liquid interface), and the catalytic action of lead oxide spontaneously appears. As a result, the PET in contact with the solid surface of the lead oxide is hydrolyzed (depolymerized) to produce terephthalic acid and ethylene glycol, and the terephthalic acid can be recovered in a state attached to the solid surface of the lead oxide (PbO2) (insoluble state), and the ethylene glycol can be recovered as an aqueous solution.
[0022] In addition, by heating the water in the reaction vessel to raise the temperature of the water, the PET chips in the water soften and the contact area with the solid lead oxide increases, which results in a stronger catalytic effect of the lead oxide at the solid-liquid interface and a faster hydrolysis rate of the PET.
[0023] Furthermore, if the reaction is carried out in a closed environment in a reaction vessel, when the temperature of the water rises above 100°C, the vapor pressure inside the reaction vessel rises and the vessel becomes pressurized. Then, the equilibrium state of the above equation (1) is lost, and the equilibrium shifts in the direction of decreasing the number of particles, as shown in the following equation (1'). (1')2H2O(PbO2 surface) ⇔ 4H + +4e - +O2⇔2H2+O2
[0024] As a result, hydrogen is generated on the solid surface of the lead oxide, and at the interface between the lead oxide and water, the hydrogen reacts with ethylene glycol, which is obtained by depolymerizing the PET, to produce methanol. The reaction formula for this is shown in Figure 2.
[0025] In other words, when the polyester resin decomposition method according to the present invention is carried out using a reaction vessel in a closed environment, hydrogen can be generated within the reaction vessel without adding hydrogen from the outside, and the organic compounds obtained by depolymerization of the polyester resin can be hydrogenated. EXAMPLES
[0026] Below, we will explain examples (experimental examples) in which the method of the present invention is applied to a process for producing sodium terephthalate and ethylene glycol or methanol using lead oxide (PbO2) as a solid oxide and crushed PET bottles as polyester resin.
[0027] Lead oxide (PbO2) is an electrode active material for lead-acid batteries, and is a common material that is distributed in large quantities around the world. Lead oxide itself is not considered a safe material, but it has been demonstrated that there are no safety issues as long as it is used in a closed reaction vessel. Therefore, in the experimental example described below, the reaction vessel was placed in an environment that was closed from the outside.
[0028] [Experimental Example 1] 1.0097 g of crushed material from collected used PET bottles (average 5 mm square, provided by Otsuka Pharmaceutical Co., Ltd., washed) was placed in a 100 mL reaction vessel (Flon Chemical NR0218). 6.5113 g of powdered lead oxide (IV) (PbO2, Kanto Chemical Co., Ltd., purity 97.0%) was added, and 50 mL of ultrapure water (18.2 MΩ cm, ELGA LabWater) was added. Then, a rugby ball-shaped stirrer (Teflon-coated) with a length of 25 mm was placed in the reaction solution, and the reaction vessel was sealed with a dedicated jig.
[0029] The reaction vessel was heated to 190° C. using a temperature controller, and then the mixture was reacted for 1 hour while maintaining the temperature at 190° C. (±5° C.) and rotating the stirrer at 20 rpm.
[0030] After that, the reaction vessel was allowed to cool naturally to room temperature, and then suction filtration was performed using a filter with a pore size of 0.025 μm (diameter 47 mm, Merck Millipore), and the components contained in the filtrate were measured. The pH of the filtrate was 6-7. In addition, a large amount of crushed PET bottles (hereinafter also referred to as crushed PET) remained on the filter along with lead oxide powder.
[0031] The components contained in the filtrate were measured using a gas chromatograph mass spectrometer (GCMS) (GCMS-QP2010 Ultra, Shimadzu Corporation). The measurement conditions for the gas chromatograph (GC) and mass spectrometry (MS) of the GCMS were set as follows:
[0032] (1)GC department Carrier gas: He. The linear velocity was controlled to 40 cm / sec and the split ratio was set to 50. Column: DB-WAX UI (30 m, diameter 0.250 mm, film thickness 0.25 μm, Agilent Technologies, Inc.) Injection temperature: 220℃ Column temperature: 50-200℃ (10℃ / min)
[0033] (2)MS department Interface temperature: 220℃ Ion source temperature: 200℃ Measurement mode: Scan mode (mass-to-charge ratio m / z 25-300)
[0034] Figure 3 is a chromatogram showing the results of GCMS analysis of the filtrate. As can be seen from this chromatogram, the predominant component in the filtrate was ethylene glycol (82%), with only small amounts of diethylene glycol (9%) and methanol (9%). Traces of formic acid were also observed.
[0035] [Experimental Example 2] The experiment was conducted in the same manner as in Experimental Example 1, except that the amount of crushed used PET bottles was changed to 1.0160 g, the amount of powdered lead (IV) oxide was changed to 6.5110 g, and the reaction time was changed to 3 hours. The same materials, containers, etc. used in the experiment were also used as in Experimental Example 1.
[0036] After the reaction, the reaction vessel was allowed to cool naturally to room temperature, and then suction filtration was performed using a 0.025 μm pore size filter (diameter 47 mm, Millipore Corporation), and the components contained in the filtrate were measured using GCMS. The pH of the filtrate was 6-7. A small amount of PET powder remained on the filter along with lead oxide powder.
[0037] The same GCMS equipment and measurement conditions were used as in Experimental Example 1. The obtained chromatogram is shown in FIG. 4. As can be seen from this chromatogram, ethylene glycol (57%) was the predominant component contained in the filtrate. Furthermore, compared to the results of Example 1, the proportion of ethylene glycol was reduced, and instead the proportions of diethylene glycol (14%) and methanol (29%) were increased. In particular, the proportion of methanol was about three times that of the results of Example 1 (9%). Acetic acid and formic acid were also observed.
[0038] [Experimental Example 3] The experiment was conducted in the same manner as in Experimental Example 1, except that the amount of crushed used PET bottles added was changed to 1.0155 g, the amount of powdered lead (IV) oxide added was changed to 6.5139 g, and the reaction time was changed to 6 hours. The same materials, containers, etc. used in the experiment were also used as in Experimental Example 1.
[0039] After the reaction, the reaction vessel was allowed to cool naturally to room temperature, and then suction filtration was performed using a 0.025μm pore size filter (diameter 47mm, Millipore Corporation), and the components contained in the filtrate were measured using GCMS. The pH of the filtrate was 6-7. Furthermore, no lead oxide powder or PET powder was found on the filter. This indicates that when the reaction temperature is 190℃, the depolymerization of PET is completed within 6 hours.
[0040] The same GCMS equipment and measurement conditions were used as in Experimental Example 1. The obtained chromatogram is shown in Figure 5. This chromatogram shows that the main component contained in the filtrate was methanol (88%), and ethylene glycol was below the detection limit. From this, it was considered that almost all of the ethylene glycol was converted to methanol. On the other hand, diethylene glycol (12%) remained without being converted to ethanol.
[0041] To confirm that terephthalic acid was attached to the surface of the lead oxide powder on the filter, the lead oxide powder was placed again in a reaction vessel (Flon Chemical NR0218) and 50 mL of ultrapure water (18.2 MΩ·cm, ELGA LabWater) and 0.44 g of sodium hydroxide were added thereto. A rugby ball-shaped stirrer (Teflon coated) with a length of 25 mm was then placed in the reaction vessel, which was then sealed with a special jig and reacted at 190°C (±5°C) for 4 hours.
[0042] The reaction vessel was then allowed to cool naturally to room temperature, after which suction filtration was performed using a filter with a pore size of 0.025 μm (diameter 47 mm, Merck Millipore). Lead oxide powder remained on the filter. The filtrate was placed in a dryer at 90°C, and the water was completely removed over 8 hours. As a result, 0.95 grams of a slightly creamy white powder was obtained. Figure 6 shows the XRD spectrum obtained from the X-ray diffraction data of this powder. Figure 7 also shows the XRD spectrum of disodium terephthalate (Tokyo Chemical Industry Co., Ltd.), a commercially available experimental reagent.
[0043] From Figures 6 and 7, it was found that the substance adhering to the lead oxide powder was disodium terephthalate, and the yield of disodium terephthalate derived from used PET was 85%.
[0044] In addition, to confirm that the lead oxide powder remaining on the filter was the same as the original lead oxide (PbO2), X-ray diffraction measurements were performed on this powder and unused lead oxide powder. As a result, the XRD spectra of the lead oxide remaining on the filter and unused lead oxide were as shown in Figures 8 and 9.
[0045] A comparison of Figures 8 and 9 indicates that lead oxide PbO2 did not change before and after the depolymerization reaction of PET, and acted as a solid-liquid interface catalyst. Figure 10 shows an electron microscope (SEM) image of unused lead oxide powder. Figure 10 shows that the lead oxide powder used in this experiment had a maximum length of about 0.1 to 3.0 μm.
[0046] [Experimental Example 4] The experiment was carried out in the same manner as in Experimental Examples 1 to 3, except that the temperature at which the PET crushed material and water were reacted in the reaction vessel using lead oxide as a solid-liquid interface catalyst was changed to 200°C (±5°C). In this experiment, the amount of used PET bottles charged was 1.0037g and the amount of powdered lead oxide charged was 6.5046g when the reaction time was 1 hour, the amount of used PET bottles charged was 1.0027g and the amount of powdered lead oxide charged was 6.5103g when the reaction time was 3 hours, and the amount of used PET bottles charged was 1.0026g and the amount of powdered lead oxide charged was 6.5123g when the reaction time was 6 hours. In each case, the amount of ultrapure water charged was 50mL. As a result of the experiment, chromatograms of the components contained in the filtrate obtained by GCMS measurement are shown in Figures 11 to 13. Figures 11, 12, and 13 show the results when the reaction time between the PET crushed material and water was 1 hour, 3 hours, and 6 hours, respectively.
[0047] As can be seen from a comparison of Figs. 11 to 13 with Figs. 3 to 5, when the reaction temperature was set at 200°C, similar results to those when the reaction temperature was set at 190°C were obtained.
[0048] [Comparative Example] As a comparative example, an experiment similar to Experimental Example 1-3 was conducted without using powdered lead oxide. That is, 1.0134 g of crushed material (average 5 mm square, provided by Otsuka Pharmaceutical Co., Ltd., cleaned) of collected used PET bottles was placed in a reaction vessel (Flon Chemical NR0218) with a capacity of 100 mL. 50 mL of ultrapure water (18.2 MΩ·cm, ELGA LabWater) was added thereto. Then, a rugby ball-shaped stirring bar (Teflon-coated) with a length of 25 mm was placed in the reaction vessel, and the reaction vessel was sealed with a dedicated jig.
[0049] This reaction vessel was heated to 200° C. with a temperature controller, and then the reaction was carried out for 72 hours while maintaining the temperature at 200° C. (±5° C.) and rotating the stirrer at 20 rpm.
[0050] After that, the reaction vessel was allowed to cool naturally to room temperature, and then suction filtration was performed using a filter with a pore size of 0.025 μm (diameter 47 mm, Merck Millipore), and the components contained in the filtrate were measured. The pH of the filtrate was 4-5. White powder remained on the filter.
[0051] The components contained in the filtrate were measured using a gas chromatograph mass spectrometer (GCMS) (GCMS-QP2010 Ultra, Shimadzu Corporation) similar to that used in the experimental example. The GCMS measurement conditions were similar to those in experimental example 1, but the column heating rate was set to 5° C. / min, slower than in experimental example 1, to carefully examine whether or not conversion from ethylene glycol to methanol was occurring.
[0052] Figure 14 is a chromatogram showing the measurement results of the filtrate. From Figure 14, it was found that ethylene glycol can be obtained from PET by extending the reaction time, even without lead oxide (PbO2) powder. On the other hand, it was confirmed that in the absence of lead oxide powder, the ethylene glycol obtained from PET is hardly converted to methanol, even if the reaction time is extended.
[0053] In addition, to confirm that the white powder remaining on the filter was terephthalic acid, X-ray diffraction measurements were performed on the white powder. The resulting XRD spectrum is shown in Figure 15, and the XRD spectrum of the standard substance is shown in Figure 16.
[0054] As can be seen from Figures 15 and 16, when PET was depolymerized using only water, terephthalic acid was recovered, but little methanol was obtained. This result was consistent with the result in Figure 14.
[0055] In addition, Patent Document 1 reports that PET can be hydrolyzed using water as a medium to obtain terephthalic acid and ethylene glycol by setting the temperature condition to 200°C to 300°C. However, it is said that the temperature condition when using thermal energy (waste heat energy) discharged from chemical plants, food plants, steel mills, cement plants, etc. is 200°C at most, and at temperature conditions of 200°C to 300°C, it is not possible to use only the waste heat energy, and an additional heat source is required. In contrast, as shown in Experimental Examples 1 to 4, the polyester resin decomposition method according to the present invention can hydrolyze PET to obtain terephthalic acid and ethylene glycol even at temperature conditions of 190°C to 200°C, and further, it is possible to convert ethylene glycol into methanol by extending the reaction time. In other words, the polyester resin decomposition method according to the present invention can utilize the waste heat energy of chemical plants, food plants, etc. without adding a heat source, and can therefore be said to be a method that can contribute to reducing carbon dioxide emissions.
[0056] [Aspects] It will be apparent to those skilled in the art that the above-described exemplary embodiments are illustrative of the following aspects.
[0057] (Item 1) A method for decomposing a polyester resin according to one aspect of the present invention comprises: The polyester resin is brought into contact with a solid oxide or hydroxide having a standard oxidation-reduction potential in water higher than the standard oxidation-reduction potential of water, thereby hydrolyzing the polyester resin.
[0058] According to the method for decomposing a polyester resin according to the first aspect, it is possible to obtain low molecular weight monomers by depolymerizing a polyester resin at low cost without using useful and expensive chemical substances as materials.
[0059] (Item 2) The method for decomposing a polyester resin according to item 2 is the method for decomposing a polyester resin according to item 1, wherein the solid is in the form of particles, powder, or granules.
[0060] According to the method for decomposing a polyester resin according to the second aspect, the contact area between the solid and the polyester resin is increased, so that the rate of hydrolysis of the polyester resin can be increased.
[0061] (Item 3) The method for decomposing a polyester resin according to item 3 is the method for decomposing a polyester resin according to item 1 or 2, wherein the solid is one or more selected from the group consisting of lead dioxide, nickel oxide, nickel hydroxide, and nickel oxyhydroxide.
[0062] (Item 4) The method for decomposing a polyester resin according to item 4 is the method for decomposing a polyester resin according to any one of items 1 to 3, wherein the polyester resin is polyethylene terephthalate (PET).
[0063] (Item 5) A method for producing methanol according to another aspect of the present invention comprises the steps of: The polyester resin is brought into contact with a solid oxide or hydroxide in water, the solid oxide or hydroxide having a standard oxidation-reduction potential in water higher than the standard oxidation-reduction potential of water, to hydrolyze the polyester resin and obtain ethanol.
[0064] In the method for producing methanol according to item 5, the solid may be in the form of particles, powder, or granules, and may be one or more selected from the group consisting of lead dioxide, nickel oxide, nickel hydroxide, and nickel oxyhydroxide. The polyester resin is preferably polyethylene terephthalate (PET).
Claims
1. A method for decomposing a polyester resin, comprising contacting the polyester resin with a solid oxide or hydroxide having a standard oxidation-reduction potential higher than that of water in neutral reaction water to hydrolyze the polyester resin.
2. The method for decomposing a polyester resin according to claim 1, wherein the solid is in the form of particles, powder or granules.
3. 3. The method for decomposing a polyester resin according to claim 1 or 2, wherein the solid is one or more selected from the group consisting of lead dioxide, nickel oxide, nickel hydroxide, and nickel oxyhydroxide.
4. 3. The method for decomposing a polyester resin according to claim 1, wherein the polyester resin is polyethylene terephthalate (PET).
5. A method for producing methanol, comprising contacting a polyester resin with a solid oxide or hydroxide having a standard oxidation-reduction potential higher than that of water in neutral reaction water, and hydrolyzing the polyester resin to obtain methanol.